Minimisation of production costs and chemical pollutants in a tin foundry plant - Martinez Miraval, Janis (2013)
The investigation consisted in the design of a mathematical model that allows the reduction of production costs in a tin foundry plant, which would lead to the reduction of pollutants. The model proposed by Kim and Lewis (1987), who was adapted to the company under study, was taken as reference. The situation that motivated this investigation was the insufficient quantitative techniques in the production programming around foundry operations, where the effect a batch has over others is not taken into account. After testing the model, the results indicated estimated savings of S/.3 314 964 per year, an estimated saving of 23% in the use of the melting furnace and a decrease in the content of pollutants.